2020
DOI: 10.1088/2053-1591/ab726e
|View full text |Cite
|
Sign up to set email alerts
|

Rational construction of Au–Ag bimetallic island-shaped nanoplates for electrocatalysis

Abstract: Active electrocatalysts are the key to water splitting for hydrogen production through the electrolysis. In this paper, 50 nm silver nanoplates were used as templates for synthesis of Au-Ag island-shaped nanoplates by controlling the surface chemistry. The guiding mechanism of polyvinylpyrrolidone (PVP, Mw=40 000) to Au-Ag island-shaped nanoplates crystal was also further investigated. It is found that the surface energy of Ag nanoplates between (100) and (111) crystal planes can be regulated by varying the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…This leads to more frequent and intense contact between the surfaces, resulting in higher friction and an increased coefficient of friction. [36][37][38] When BN or B 4 C particles are added, they can act as lubricants or protective agents between the surfaces, reducing direct metal-to-metal contact and friction. At an optimal particle content, the particles effectively fill surface defects, aid in smooth sliding, and reduce friction, resulting in a lower coefficient of friction.…”
Section: Coefficient Of Frictionmentioning
confidence: 99%
“…This leads to more frequent and intense contact between the surfaces, resulting in higher friction and an increased coefficient of friction. [36][37][38] When BN or B 4 C particles are added, they can act as lubricants or protective agents between the surfaces, reducing direct metal-to-metal contact and friction. At an optimal particle content, the particles effectively fill surface defects, aid in smooth sliding, and reduce friction, resulting in a lower coefficient of friction.…”
Section: Coefficient Of Frictionmentioning
confidence: 99%
“…47 Their study intricately elucidated the atomic arrangements of these single-layer metal nanoislands on Au(111), providing comprehensive insights into their geometric, energetic, and electronic attributes. Other works have also reported that Pd or Pt on Au(111) commonly forms single-layer nanoislands, [33][34][35][36][37][38][39][40][41][42][43][44][48][49][50][51][52][53] while explorations have also extended to investigating bimetallic nanoislands, such as Ni/Au, [54][55][56][57][58][59] Cu/Au, [60][61][62][63][64] Rh/Au, [65][66][67][68][69][70] Pd-Rh/Au, 71 Ag/Au, 72,73 Ir/Au, 52 Au-Ag, 74 Ir/Ni, 52 Ag/Cu, 75 Rh/Pd, 76 Pd/Pt, 45 Ir/Pt, 52 and Pt/Cu. 77 In the present study, we conducted a thoro...…”
Section: Introductionmentioning
confidence: 99%